Wide-temperature-range thermoelectric n-type Mg3(Sb,Bi)2 with high average and peak zT values - Li, Jing-Wei; Han, Zhijia; Yu, Jincheng; Zhuang, Hua-Lu; Hu, Haihua; Su, Bin; Li, Hezhang; Jiang, Yilin; Chen, Lu; Liu, Weishu; Zheng, Qiang; Li, Jing-Feng (Nature communications, 2023)
Mg 3 (Sb,Bi) 2 is a promising thermoelectric material suited for electronic cooling, but there is still room to optimize its low-temperature performance. This work realizes >200% enhancement in room-temperature zT by incorporating metallic inclusions (Nb or Ta) into the Mg 3 (Sb,Bi) 2 -based matrix. The electrical conductivity is boosted in the range of 300–450 K, whereas the corresponding Seebeck coefficients remain unchanged, leading to an exceptionally high room-temperature power factor >30 μW cm −1 K −2 ; such an unusual effect originates mainly from the modified interfacial barriers. The reduced interfacial barriers are conducive to carrier transport at low and high temperatures. Furthermore, benefiting from the reduced lattice thermal conductivity, a record-high average zT > 1.5 and a maximum zT of 2.04 at 798 K are achieved, resulting in a high thermoelectric conversion efficiency of 15%. This work demonstrates an efficient nanocomposite strategy to enhance the wide-temperature-range thermoelectric performance of n-type Mg 3 (Sb,Bi) 2 , broadening their potential for practical applications. The utilization of Mg 3 (Sb,Bi) 2 in thermoelectric devices is hindered by its low performance near room temperature. Here, authors report thermoelectric performance enhancement of Mg 3 (Sb,Bi) 2 within a wide temperature range by incorporating metallic inclusions at grain boundaries. (279 in total)